Electrolytes for metal-ion battery cells with high-capacity, micron-scale, volume-changing anode particles

Specialized electrolyte compositions for rechargeable batteries with micron-scale, volume-changing anodes and cathodes enhance cycling stability and energy density by stabilizing the SEI layer and reducing binder swelling, addressing the performance issues of conventional electrolytes.

JP7607699B2Active Publication Date: 2024-12-27SILA NANOTECHNOLOGIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023061910
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-11
Filing Date
2023-04-06
Publication Date
2024-12-27
Estimated Expiration
2038-09-12

AI Technical Summary

Technical Problem

Conventional electrolytes fail to optimize the performance of rechargeable batteries with micron-scale, volume-changing anode particles, leading to poor cell performance characteristics and limited cycling stability due to high volume changes and inadequate electrode density, which affects energy density and manufacturing costs.

Method used

Development of specialized electrolyte compositions that stabilize the solid electrolyte interphase (SEI) layer and reduce binder swelling, utilizing a combination of low and room temperature solvents, additives, and salt concentrations to enhance the performance of high-capacity nanocomposite anodes and cathodes with moderate to high volume changes.

Benefits of technology

The electrolyte compositions significantly improve the cycling stability, energy density, and rate performance of batteries with micron-scale anode particles, overcoming the limitations of conventional electrolytes by maintaining a stable SEI layer and reducing binder modulus changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607699000001
    Figure 0007607699000001
  • Figure 0007607699000002
    Figure 0007607699000002
  • Figure 0007607699000003
    Figure 0007607699000003
Patent Text Reader

Abstract

To provide a lithium-ion battery cell with improved cycle operation, rate capability, etc.SOLUTION: A lithium-ion battery cell includes an anode electrode 102, a cathode electrode 103, a separator 104, and an electrolyte that ionically couples the anode and cathode electrodes. The anode electrode is a high capacity electrode (for example, in the range of about 2 mAh / cm2 to about 10 mAh / cm2). The electrolyte includes a solvent composition, and the solvent composition includes a low melting point (LMP) solvent in the range of about 10 vol.% to about 80 vol.% of the solvent composition, and normal melting point (RMP) solvents in the range of about 20 vol.% to about 90 vol.% of the solvent composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This patent application claims priority to U.S. Non-provisional Patent Application No. 16 / 128,340, filed September 11, 2018, entitled "Electrolyte for a Metal-Ion Battery Cell with High-Capacity, Micron-Scale, Volume-Changing Anode Particles," and U.S. Provisional Patent Application No. 62 / 557,416, filed September 12, 2017, entitled "Improved Liquid Electrolytes for Cells with High-Capacity Anodes based on Micron-Scale Volume-Changing Particles," each of which is expressly incorporated by reference herein in its entirety.

[0002] Field The present disclosure relates generally to energy storage devices, and more particularly to battery technology. [Background technology]

[0003] background Due in part to their relatively high energy density, relatively high specific energy, light weight and potential for long life, advanced rechargeable batteries are desirable for a wide range of consumer electronics, electric vehicles, grid storage and other important applications.

[0004] However, despite the increasing commercial popularity of batteries, further development of these batteries is needed, especially for applications in low or zero emission hybrid electric or fully electric vehicles, consumer electronics, wearable devices, energy saving cargo ships and locomotives, drones, aerospace applications, and power grids. In particular, further improvements are desired for various rechargeable batteries, such as rechargeable Li and Li-ion batteries, rechargeable Na and Na-ion batteries, rechargeable K and K-ion batteries, rechargeable Ca and Ca-ion batteries, and rechargeable Mg and Mg-ion batteries, to name a few.

[0005] A wide range of electrolyte compositions can be utilized in the construction of Li and Li-ion batteries as well as other metal and metal-ion batteries. However, for improved cell performance (e.g., low and stable resistance, high cycling stability, high rate capability, etc.), it is necessary to develop an optimal selection of electrolyte for the specific type and specific size of active particles in both the anode and cathode, as well as the specific operating conditions (e.g., temperature, charge rate, discharge rate, voltage range, capacity utilization, etc.). In many cases, the selection of electrolyte components and their ratios can be non-trivial and counter-intuitive.

[0006] In certain types of rechargeable batteries, charge-storing anode materials can be produced as high-capacity (nano)composite powders that exhibit moderately high volume change (e.g., 8-180 vol.%) during the first charge-discharge cycle, and moderate volume change (e.g., 5-50 vol.%) during subsequent charge-discharge cycles. A subset of such charge-storing anode particles includes anode particles having an average size (e.g., diameter or thickness) in the range of about 0.2 to about 40 microns. Such a class of charge-storing particles offers great prospects for scalable manufacturing and achieving high cell-level energy density and other performance features. Unfortunately, such particles are relatively new, and their use in cells employing conventional electrolytes can lead to relatively poor cell performance characteristics and limited cycling stability. High-capacity (nano)composite anodes have moderate capacity loadings (areal capacity) (e.g., 2-4 mAh / cm2). 2 ) and for even higher areal capacities (e.g., 4–10 mAh / cm 2 ), cell performance may be particularly poor. However, higher capacity loading is advantageous for increasing cell energy density and lowering cell manufacturing costs. Similarly, cell performance may be degraded if the porosity of such anodes (e.g., the volume occupied by the space between the (nano)composite active anode particles in the electrode and filled with electrolyte) becomes moderately small (e.g., 25-35 vol.%) after the first charge-discharge cycle, and more if the porosity of the anodes becomes small (e.g., 5-25 vol.%) after the first charge-discharge cycle, or if the amount of binder and conductive additive in the electrode becomes moderately small (e.g., 5-15 wt.%), and more if the amount of binder and conductive additive in the electrode becomes small (e.g., 0.5-5 wt.%). However, higher electrode density and lower binder and conductive additive content are advantageous for increasing cell energy density and lowering costs. Lower binder content may also be advantageous for increasing cell rate performance.

[0007] Examples of materials that exhibit moderately high volume changes (e.g., 8-180 vol.%) during the first charge-discharge cycle and moderate volume changes (e.g., 5-50 vol.%) during subsequent charge-discharge cycles include so-called conversion type (including both so-called chemical conversion and so-called "true conversion" subclasses), as well as (nano)composites, including so-called alloy type active electrode materials. For metal-ion batteries (e.g., Li-ion batteries), examples of such conversion type active electrode materials include, but are not limited to, metal fluorides (e.g., lithium fluoride, iron fluoride, copper fluoride, bismuth fluoride, mixtures and alloys thereof, etc.), metal chlorides, metal iodides, metal bromides, metal chalcogenides (e.g., sulfides, including lithium sulfide and other metal sulfides), sulfur, selenium, metal oxides (including but not limited to lithium oxide and silicon oxide), metal nitrides, metal phosphides (including lithium phosphide), metal hydrides, etc. For metal-ion batteries (e.g., Li-ion batteries), examples of such alloy-type electrode materials include, but are not limited to, silicon, germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, lead, bismuth, their alloys, and the like. These materials typically offer higher gravimetric and volumetric capacity than the so-called intercalated electrodes commonly used in commercial metal-ion (e.g., Li-ion) batteries. Alloy-type electrode materials are particularly advantageous for use in certain high-capacity anodes for Li-ion batteries. Silicon-based alloy-type anodes may be particularly attractive for such applications.

[0008] Thus, there is a continuing need for improved batteries, components and other related materials and methods of manufacture. Summary of the Invention

[0009] SUMMARY OF THE DISCLOSURE The embodiments disclosed herein address the above-mentioned needs by providing improved batteries, components, and other related materials and methods of manufacture.

[0010] As an example, a metal ion battery cell may include an anode and a cathode electrode, the anode electrode having a capacity of about 2 mAh / cm 2 ~about 10mAh / cm 2 % to about 180 vol.%, (i) having an average particle size in the range of about 0.2 microns to about 20 microns, (ii) exhibiting a volume expansion in the range of about 8 vol.% to about 180 vol.% during one or more charge-discharge cycles of the battery cell, and (iii) exhibiting a specific capacity in the range of about 550 mAh / g to about 2200 mAh / g. The metal-ion battery cell further includes a separator electrically separating the anode electrode and the cathode electrode, and an electrolyte ionically coupling the anode electrode and the cathode electrode, the electrolyte including one or more metal ion salts and a solvent composition. The solvent composition comprises one or more low melting point solvents, each having a melting point in the range of about -140°C to about -60°C, and comprising about 10 vol.% to about 80 vol.% of the solvent composition, and one or more normal melting point solvents, each having a melting point in the range of about -60°C to about +30°C, and comprising about 20 vol.% to about 90 vol.% of the solvent composition.

[0011] The accompanying drawings are presented to aid in the explanation of embodiments of the present disclosure and are provided for illustration only and not for limitation of the embodiments. Unless otherwise stated or implied by context, different shading, shading and / or fill patterns in the drawings are meant only to depict distinctions between different components, elements, features, etc., and are not meant to suggest the use of particular materials, colors or other characteristics that may be defined outside of this disclosure for the specific patterns used. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 illustrates an example Li-ion battery in which the components, materials, methods and other techniques described herein may be implemented. [Diagram 2] FIG. 1 is a diagram showing an example of a suitable electrolyte component selection. [Figure 3A]FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of full cells containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. Typical charge-discharge curves for cycle 1 and cycle 5. [Figure 3B] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of full cells containing (nano)composite anodes exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 shows the electrochemical stability of example cells, with specific capacity normalized by the weight of the active anode material. [Figure 4A] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of a full cell containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of some example electrolyte compositions on the performance of cycled cells. [Figure 4B] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of a full cell containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of some example electrolyte compositions on the performance of cycled cells. [Diagram 5] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of full cells containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of salt concentration on the performance of low and high electrode capacity loading cells. [Figure 6]FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of a full cell comprising a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of example electrolyte compositions on the performance of cycled cells. [Figure 7A] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of a full cell containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of other example electrolyte compositions on the performance of cycled cells. [Figure 7B] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of a full cell containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of other example electrolyte compositions on the performance of cycled cells. [Figure 7C] FIG. 1 shows the effect of example electrolyte compositions on the performance characteristics of a full cell containing a (nano)composite anode exhibiting high capacity and moderately high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. FIG. 2 illustrates the effect of other example electrolyte compositions on the performance of cycled cells. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Aspects of the invention are disclosed in the following description and associated drawings directed to specific embodiments of the invention. The term "embodiments of the invention" does not necessarily require that all embodiments of the invention include the discussed features, advantages, methods or modes of operation, and alternative embodiments may be devised without departing from the scope of the invention. Additionally, well-known elements of the invention may not be described in detail or may be omitted so as not to obscure other, more relevant details.

[0014] Any numerical range described herein with respect to any embodiment of the invention is intended not only to define the upper and lower limits of the relevant numerical range, but also to implicitly disclose each individual value within that range in units or increments consistent with the level of precision by which the upper and lower limits are characterized. For example, a numerical distance range of 7 nm to 20 nm (i.e., a precision level of 1 unit or increment) encompasses the set [7, 8, 9, 10, ..., 19, 20] (units in nm), as if the intervening numbers from 8 to 19 in units or increments of 1 were explicitly disclosed. In another example, a temperature range of about -120°C to about -60°C encompasses the set of temperature ranges (units in °C) of about -120°C to about -119°C, about -119°C to about -118°C, ... about -61°C to about -60°C, as if the intervening numbers (units in °C) between -120°C to -60°C in the increment range were explicitly disclosed. In yet another example, a numerical percentage range of 30.92% to 47.44% (i.e., at the level of precision of hundredths or increments) encompasses the set (units %) of [30.92, 30.93, 30.94, ..., 47.43, 47.44], as if the intervening numerical values ​​between 30.92 and 47.44 in hundredths or increments were expressly disclosed. Thus, it is intended that any intervening numerical values ​​encompassed within any disclosed numerical range be construed as if those intervening numerical values ​​were explicitly disclosed, whereby any such intervening numerical values ​​may constitute their own inherent upper and / or lower limits of subranges falling within the broader range. Each subrange (e.g., each range that includes at least one intervening numerical value from the broader range as an upper and / or lower limit) is thereby intended to be construed as being implicitly disclosed by the explicit disclosure of the broader range.

[0015] The following description may describe specific examples in the context of Li and Li-ion batteries (for brevity and convenience, and because Li technology is currently common), but it should be recognized that various embodiments may be applicable to other rechargeable and primary batteries (such as Na-ion, Mg-ion, K-ion, Ca-ion and other metal and metal-ion batteries). Additionally, while the following description may also describe specific examples of material formulations in a Li-free state (e.g., for silicon-containing nanocomposite anodes), it should be recognized that various embodiments may be applicable to Li-containing electrodes and active materials (e.g., partially or fully lithiated Si-containing anodes, partially or fully lithiated metal fluoride-containing cathodes (e.g., mixtures of LiF with metals such as Cu, Fe, Cu-Fe alloys, various other alloys and mixtures of metals, etc.), partially or fully lithiated chalcogenides (e.g., LiS, LiS / metal mixtures, LiSe, LiSe / metal mixtures, LiS-LiSe mixtures, various other compositions including lithiated chalcogenides, etc.), partially or fully lithiated metal oxides (e.g., LiO, LiO / metal mixtures, etc.), among others).

[0016] Furthermore, although the following description may describe specific examples in the context of some specific alloy-type and conversion-type chemistries of anode and cathode active materials for Li-ion batteries (e.g., silicon-containing anodes or metal fluoride-containing or lithium sulfide-containing cathodes), it should be recognized that the various embodiments may be applicable to other chemistries for Li-ion batteries (other conversion-type and alloy-type electrodes, as well as various intercurrent-type electrodes), as well as other battery chemistries. For metal-ion batteries (e.g., Li-ion batteries), examples of other suitable conversion-type electrodes include, but are not limited to, metal chlorides, metal iodides, metal bromides, sulfur, selenium, metal oxides, metal nitrides, metal phosphides, metal hydrides, and the like.

[0017] During battery (e.g., Li-ion) operation, conversion materials change (transform) from one crystal structure to another (hence the name "conversion" type). This process involves breaking chemical bonds and forming new bonds. During (e.g., Li-ion) battery operation, Li ions are inserted into alloy-type materials and a lithium alloy is formed (hence the name "alloy" type). Sometimes "alloy" type electrode materials are considered a subclass of "conversion" type electrode materials.

[0018] 1 shows an example of a metal-ion (e.g., Li-ion) battery to which the components, materials, methods, and other techniques described herein, or combinations thereof, may be applied according to various embodiments. A cylindrical battery is shown here for illustrative purposes, but other types of configurations, including prismatic or pouch (laminated) batteries, may be used as desired. The example battery 100 includes a negative anode 102, a positive cathode 103, a separator 104 located between the anode 102 and the cathode 103, an electrolyte (implied) that impregnates the separator 104, a battery case 105, and a sealant 106 that seals the battery case 105.

[0019] Conventional electrolytes for this type of Li or Na based batteries generally consist of 0.8-1.2M (1M±0.2M) solutions of Li or Na single salts (e.g., LiPF6 for Li-ion batteries and NaPF6 or NaClO4 salts for Na-ion batteries) in a mixture of carbonate solvents with 1-2 wt.% of other organic additives. Common organic additives may include nitriles, esters, sulfones, sulfoxides, phosphorus-based solvents, silicon-based solvents, ethers, etc. Such additive solvents may be modified (e.g., sulfonated or fluorinated).

[0020] The conventional salt used in most conventional Li-ion battery electrolytes is LiPF6. Examples of less common salts (e.g., those that have been primarily investigated in research publications or, in some cases, not even described in Li-ion battery electrolyte applications, but may still be applicable and useful) include lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroantimonate (LiSbF6), lithium hexafluorosilicate (Li2SiF6), lithium hexafluoroaluminate (Li3AlF6), lithium bis(oxalato)borate (LiB(C2O4)2, lithium difluoro(oxalato)borate (LiBF2(C2O4)), various lithium imides (e.g., SO2FN), lithium hexafluorosilicate (Li2SiF6), lithium hexafluoroaluminate (Li3AlF6), lithium bis(oxalato)borate (LiB(C2O4)2, lithium difluoro(oxalato)borate (LiBF2(C2O4)), lithium hexafluorosilicate (Li2SiF6), lithium hexafluorosilicate (Li2SiF6), lithium hexafluoroaluminate (Li3AlF6), lithium bis(oxalato)borate (LiB(C2O4)), lithium difluoro(oxalato)borate (LiBF2(C2O4)), lithium hexafluorosilicate (Li2SiF6 ... - (Li + )SO2F, CF3SO2N - (Li + )SO2CF3, CF3CF2SO2N - (Li + )SO2CF3, CF3CF2SO2N - (Li + )SO2CF2CF3, CF3SO2N - (Li + )SO2CF2OCF3, CF3OCF2SO2N - (Li + )SO2CF2OCF3, C6F5SO2N - (Li + )SO2CF3, C6F5SO2N - (Li + )SO2C6F5 or CF3SO2N - (Li + )SO2PhCF3, etc.

[0021] Electrodes utilized in Li-ion batteries are typically produced by (i) forming a slurry containing the active material, conductive additives, a binder solution, and in some cases surfactants or other functional additives, (ii) casting the slurry onto a metal foil (e.g., Cu foil for most anodes and Al foil for most cathodes), and (iii) drying the cast electrode to completely evaporate the solvent.

[0022] Conventional anode materials utilized in Li-ion batteries are of the intercalating type. Metal ions are intercalated and occupy the interstitial sites of such materials during charging or discharging of the battery. Such anodes undergo small or very small volume changes when used in electrodes. Polyvinylidene fluoride or difluoride (PVDF) and carboxymethyl cellulose (CMC) are the two most common binders used in these electrodes. Carbon black is the most common conductive additive used in these electrodes. However, such anodes have relatively small gravimetric and volumetric capacities (typically less than 370 mAh / g rechargeable specific capacity for graphite or hard carbon based anodes and 600 mAh / cm at the electrode level not considering the volume of the current collector foil). 3 Rechargeable volume capacity (less than 1000mAh).

[0023] Alloy-type anode materials for use in Li-ion batteries offer higher gravimetric and volumetric capacities compared to intercalated anodes. For example, silicon (Si) offers approximately 10 times higher gravimetric capacity and approximately 3 times higher volumetric capacity compared to intercalated graphite (or graphite-like) anodes. However, Si suffers from significant volume expansion (up to approximately 300 vol.%) during Li insertion, which can therefore induce thickness changes and mechanical failure of Si-containing anodes. Furthermore, Si (and some Li-Si alloy compounds that can be formed during the lithiation of Si) suffer from relatively low electrical conductivity and relatively low ionic (Li-ion) conductivity. The electrical and ionic conductivity of Si is lower than that of graphite. The formation of (nano)composite Si-containing particles (including but not limited to Si-carbon composites, Si-metal composites, Si-polymer composites, Si-ceramic composites, composites containing nanostructured Si, various combinations of carbon, polymer, ceramic and metal, or other types of porous composites containing nanostructured Si, or nanostructured or nano-sized Si particles of various shapes and morphologies) can reduce the volume change during Li-ion insertion and extraction, which in turn can lead to better cycling stability of rechargeable Li-ion cells.

[0024] In addition to Si-containing nanocomposite anodes, other examples of such nanocomposite anodes containing alloy-type active materials include, but are not limited to, those containing germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, lead, bismuth, alloys thereof, and the like.

[0025] In addition to (nano)composite anodes containing alloy-type active materials, other interesting types of high capacity (nano)composite anodes may include metal oxides (including silicon oxide, lithium oxide, etc.), metal nitrides, metal phosphides (including lithium phosphide), metal hydrides, etc.

[0026] In particular, high capacity (nano)composite anode powders exhibiting moderately high volume change (e.g., about 8 to about 180 vol.%) during the first charge-discharge cycle, moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles, and average sizes ranging from about 0.2 to about 40 microns (and more preferably, in some applications, from about 0.4 to about 20 microns) may be particularly attractive for battery applications in terms of manufacturability and performance characteristics. 2 ) to high (e.g., about 4 to about 10 mAh / cm 2 ) electrodes with electrode areal capacity loading are also particularly attractive for use in cells. In some designs, the near-spherical (ellipsoidal) shape of these composite particles may be very attractive for further increasing the rate capability and volumetric capacity of the electrode. However, despite some improvements that may be achieved by the formation and utilization of such alloy-type or conversion-type active materials, including nanocomposite anode materials and electrode formulations, substantial further improvements in cell performance characteristics may be achieved by improved composition and preparation of electrolytes (e.g., liquid electrolytes) beyond those known or indicated by the prior art. Unfortunately, high capacity (nano)composite anode and cathode powders are relatively new, exhibiting moderately high volume changes during the first charge-discharge cycle (e.g., about 8 to about 180 vol.%), moderate volume changes during subsequent charge-discharge cycles (e.g., about 4 to about 50 vol.%), average sizes in the range of about 0.2 to about 40 microns, and relatively low densities (e.g., about 0.5 to 3.8 g / cc), and their performance characteristics and limited cycling stability are typically poor, especially at moderate electrode area capacity loadings (e.g., about 2 to about 4 mAh / cm). 2 ), and the electrode area capacity loading is high (e.g., about 4 to about 10 mAh / cm 2) is relatively inadequate. However, higher capacity loading is advantageous for increasing cell energy density and lowering cell manufacturing costs. Similarly, cell performance may be worse when such electrode (e.g., anode) porosity (volume occupied by the space between the (nano)composite active anode particles in the electrode and filled with electrolyte) is moderately small (e.g., about 25 to about 35 vol.%), and more when the electrode porosity is small (e.g., about 5 to about 25 vol.%), or when the amount of binder and conductive additive in the electrode is moderately small (e.g., about 6 to about 15 wt.%), and more when the amount of binder and conductive additive in the electrode is small (e.g., about 0.5 to about 5 wt.%). However, higher electrode density and lower binder content are advantageous for increasing cell energy density and lowering costs in certain applications. Lower binder content may also be advantageous for increasing cell rate performance. Larger volume changes result in inferior performance in some designs, which may be related to damage to the solid electrolyte interphase (SEI) layer that forms on the anode, non-uniform lithiation and delithiation of electrode particles within the electrode, and other factors.

[0027] Surprisingly, the inventors have found that electrolyte compositions that work well with intercalated anode and cathode electrodes (of various particle sizes), and electrolytes that show improved performance for nano-sized (e.g., in the range of about 1 nm to about 200 nm) conversion-type anode materials and conversion-type cathode materials or nano-sized (typically in the range of 1 nm to 200 nm) alloy-type anode materials, do not perform well in cells containing high-capacity (nano)composite anode particles (e.g., powders) that exhibit moderately high volume changes (e.g., about 8 to about 180 vol.%) during the first charge-discharge cycle, moderate volume changes (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles, and average sizes in the range of about 0.2 to about 40 microns. Moreover, electrolytes that typically do not perform well in cells containing conventional nano-sized (e.g., in the range of about 1 nm to about 200 nm) alloy-type anodes have been found to perform remarkably well in cells containing high-capacity (nano)composite anode particles (e.g., powders) that exhibit moderately high volume changes (e.g., about 8 to about 180 vol.%) during the first charge-discharge cycle, moderate volume changes (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles, and average sizes in the range of about 0.2 to about 40 microns. The effect of changes in electrolyte composition on otherwise improved cell performance with such (nano)composite anodes containing alloy-type anode materials has been found to be particularly strong in certain applications. In particular, electrolytes that exhibit a volume change of about 0.5 m 2 / g~about 50m 2Identifying electrolyte compositions for improved performance of such anode powder subclasses having specific surface areas in the range of 1000 mAh / g has been found to be particularly beneficial and impactful for achieving a combination of good stability, good energy density and other performance features. In one example, for anode materials containing silicon (Si), (nano)composite electrodes having gravimetric capacities (normalized by the total combined mass of (nano)composite particles, binder and conductive additive) in the range of about 600 mAh / g to 2200 mAh / g or about 2600 mAh / g have been particularly beneficial, as the combination of the disclosed electrolyte compositions with such anodes allows cells to achieve an attractive combination of good stability, good energy density, good rate capability and other important and desired performance features.

[0028] One or more embodiments of the present disclosure provide a wide range of batteries that experience consistent volume changes during cycling (e.g., moderately high volume changes (e.g., about 8 to about 160 or about 180 vol.%) during the first charge-discharge cycle and moderate volume changes (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles), average particle sizes in the range of about 0.2 to about 40 microns, and average particle sizes in the range of about 0.5 to about 50 microns. 2 This overcomes some of the challenges discussed above for various types of cells that include nanocomposite anode materials (e.g., materials that include conversion-type and alloy-type active materials) with specific surface areas in the range of 0.1 to 1.0 mAh / cm. According to one or more embodiments, substantially more stable cells can be achieved with a medium (e.g., about 2 to about 4 mAh / cm. 2 ) and high capacity load (e.g., about 4 to about 10 mAh / cm 2 ), high packing density (electrode porosity filled with electrolyte after the first charge-discharge cycle in the range of about 5 to about 35 vol.%), and relatively low binder content (e.g., about 0.5 to about 14 wt.%).

[0029] Conventional cathode materials utilized in Li-ion batteries are of the intercalated type and generally crystalline. Such cathodes typically have a maximum charge potential of less than about 4.3 V vs. Li / Li+, a gravimetric capacity (relative to the mass of active material) of less than about 190 mAh / g, and a charge capacity of less than about 800 mAh / cm. 3 The results show a volumetric capacity (relative to the volume of the electrode, not including the volume occupied by the current collector foil) of less than 10 ... Combining such types of higher energy density cathodes with high capacity (e.g., Si-based) anodes can lead to high cell-level energy densities. Unfortunately, the cycling stability and other performance characteristics of such cells, at least when used in combination with conventional electrolytes, may not be sufficient for some applications.

[0030] Thereby, one or more embodiments of the present disclosure provide a subclass of high voltage intercalating cathodes (cathodes having a maximum charging potential in the range of about 4.2 V to about 4.5 V vs. Li / Li+, and in some cases about 4.5 V vs. Li / Li+ to about 5.1 V vs. Li / Li+) and high capacity moderate volume change anodes (e.g., a moderately high volume change (e.g., about 8 to about 160 or about 180 vol.%) during the first charge-discharge cycle, a moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles, an average size (e.g., average diameter) in the range of about 0.2 to about 40 microns, and a mean size (e.g., average diameter) of about 0.5 to about 50 m normalized by the mass of the composite electrode particles). 2 The present invention is directed to electrolyte compositions that work well in combination with anodes comprising (nano)composite anode powders that exhibit specific surface areas in the range of about 550 to about 2200 mAh / g or about 2700 mAh / g (when normalized by the total mass of the composite anode particles, conductive additive, and binder), or specific capacities in the range of about 650 to about 2200 mAh / g or about 2900 mAh / g (when normalized by the mass of the composite anode particles alone) for Si-containing anodes. In at least one embodiment, a particular electrolyte composition may be selected based on the value of the highest cathode charging potential.

[0031] Examples of high specific capacity and high volumetric capacity conversion type cathode materials include, but are not limited to, fluorides, chlorides, sulfides, selenides, etc. For example, fluoride-based cathodes have in some cases exceeded 300 mAh / g (1200 mAh / cm at the electrode level). 3For example, in the Li-free state, FeF3 exhibits a theoretical specific capacity of 712 mAh / g, FeF2 exhibits a theoretical specific capacity of 571 mAh / g, MnF3 exhibits a theoretical specific capacity of 719 mAh / g, CuF2 exhibits a theoretical specific capacity of 528 mAh / g, NiF2 exhibits a theoretical specific capacity of 554 mAh / g, PbF2 exhibits a theoretical specific capacity of 219 mAh / g, and BiF3 exhibits a theoretical specific capacity of 302 mAh / g. ZnF2 presents a theoretical specific capacity of 519mAh / g, BiF5 presents a theoretical specific capacity of 441mAh / g, SnF2 presents a theoretical specific capacity of 342mAh / g, SnF4 presents a theoretical specific capacity of 551mAh / g, SbF3 presents a theoretical specific capacity of 450mAh / g, SbF5 presents a theoretical specific capacity of 618mAh / g, CdF2 presents a theoretical specific capacity of 356mAh / g, and ZnF2 presents a theoretical specific capacity of 519mAh / g. AgF and AgF2 also present a theoretical specific capacity and also show very high lithiation capacity. Mixtures of fluorides (e.g., in the form of alloys) can present theoretical capacities estimated according to the rule of mixtures. The use of mixed metal fluorides can sometimes be advantageous (e.g., can present higher rates, lower resistance, higher practical capacity, or longer stability). The use of metal fluorides mixed with metals can also be advantageous in some cases (e.g., may exhibit higher rates, lower resistance, higher practical capacity, or longer stability). In the fully lithiated state, the metal fluoride converts to a composite containing a mixture of metal and LiF clusters (or nanoparticles). Examples of globally reversible reactions of conversion metal fluoride cathodes include 2Li+CuF2⇔2LiF+Cu for CuF2-based cathodes, or 3Li+FeF3⇔3LiF+Fe for FeF3-based cathodes. It should be recognized that metal fluoride-based cathodes can be prepared both in Li-free, partially lithiated, or fully lithiated states. Another example of a promising conversion cathode (or anode, in some cases) material is sulfur (S) (Li-free state) or lithium sulfide (Li2S, fully lithiated state).To reduce dissolution of the active material during cycling, improve the electrical conductivity, or improve the mechanical stability of the S / Li2S electrode, the formation of porous S, Li2S, porous SC composites, Li2S-C composites, porous S-polymer composites, or other composites containing S or Li2S or both can be utilized.

[0032] It should be noted that in some designs, different electrolyte compositions may provide the most favorable performance for cells containing the same anode (e.g., a Si-containing nanocomposite anode) and different cathodes (intercalated type, high voltage intercalated type, S-containing conversion type, F-containing conversion type, etc.).

[0033] Unfortunately, many conversion type electrodes used in Li-ion batteries suffer from performance limitations. The formation of (nano)composites may overcome such limitations, at least in part. For example, certain (nano)composites may result in reduced voltage hysteresis, improved capacity utilization, improved rate capability, improved mechanical and sometimes improved electrochemical stability, reduced volume change, and / or other beneficial attributes. Examples of such composite cathode materials include LiF-Cu-Fe-C nanocomposites, LiF-Cu-Fe-Ag-C nanocomposites, LiF-Cu-Fe-Ti-C nanocomposites, LiF-Cu-Fe-Mn-C nanocomposites, FeF2-C nanocomposites, FeF3-C nanocomposites, CuF2-C nanocomposites, CuF2-C-AlF3 nanocomposites, CuF2-C-Al2O3 nanocomposites. 、These include, but are not limited to, LiF-Cu-C nanocomposites, LiF-Cu-C-polymer nanocomposites, LiF-Cu-another metal-C-polymer nanocomposites, LiF-Cu-another metal oxide-C-polymer nanocomposites, LiF-Cu-another metal fluoride-C-polymer nanocomposites, LiF-Cu-metal-polymer nanocomposites, and many other porous nanocomposites containing LiF, FeF3, FeF2, MnF3, CuF2, NiF2, PbF2, BiF3, BiF5, CoF2, SnF2, SnF4, SbF3, SbF5, CdF2, ZnF2, AgF, AlF3, AgF2 or other metal fluorides or mixtures thereof. Such composites may also contain oxides and oxyfluorides, and may be conductive (mainly sp 2 -bonded) carbon. In some examples, metal fluoride nanoparticles may infiltrate the pores of porous carbon (e.g., the pores of activated carbon particles) to form these metal fluoride-C or mixed metal-LiF-another metal oxide or metal fluoride-C nanocomposites, among other related compositions. In particular, high capacity (nano)composite cathode particles (e.g., powders) exhibiting moderately high (for the cathode) volume change (e.g., about 5 to about 100 vol.%) during the first charge-discharge cycle, moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles, and average size (e.g., diameter in the case of spherical particles, or thickness in the case of flat particles, or average dimension in the case of randomly shaped particles) in the range of about 0.2 to about 40 microns may be particularly attractive for battery applications in terms of manufacturability and performance characteristics. In some designs, near-spherical (ellipsoidal) shaped composite cathode particles may further be highly attractive for optimizing the rate performance and volumetric capacity of the electrode. However, notwithstanding some improvements that may be achieved through the formation and utilization of such converted nanocomposite cathode materials and electrode optimization, further improvements in cell performance characteristics may be achieved through improved composition and preparation of the electrolyte beyond that known or indicated by the prior art.

[0034] Thereby, one or more embodiments of the present disclosure provide an electrolyte composition that works well in combination with (i) a high capacity conversion type (nano)composite cathode material that exhibits a moderate volume change (e.g., about 5 to about 50 vol.%) during the first charge-discharge cycle, and a small to moderate volume change (e.g., about 3 to about 40 vol.%) during subsequent charge-discharge cycles, and an average size (e.g., diameter, for spherical particles) in the range of about 0.2 to about 40 microns, and (ii) a subclass of high capacity moderate volume change anodes, where the anodes exhibit a moderately high volume change (e.g., about 8 to about 160 or about 180 vol.%) during the first charge-discharge cycle, a moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles, an average size (e.g., average diameter) in the range of about 0.2 to about 40 microns, and an average size (e.g., average diameter) in the range of about 0.5 to about 50 microns normalized by the mass of the active electrode particles. 2 The present invention relates to an electrolyte composition comprising a (nano)composite anode powder exhibiting a specific surface area in the range of about 550 to about 2200 mAh / g or about 2700 mAh / g (when normalized by the total mass of the composite electrode particles, conductive additive and binder), or a specific capacity in the range of about 650 to about 2200 mAh / g or about 2900 mAh / g (when normalized by the mass of the composite anode particles alone) for a Si-containing anode.

[0035] The inventors have found that cells including electrodes based on high capacity nanocomposite particles or powders (including conversion or alloy type active materials) undergoing constant volume change during cycling (moderately high volume change (e.g., about 8 to about 180 vol.% increase or about 8 to about 70 vol.% decrease) during the first charge-discharge cycle and moderate volume change (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles) and average sizes in the range of about 0.2 to about 40 microns (e.g., Si-based nanocomposite anode powders, among many others) can benefit from certain compositions of electrolytes that result in significantly improved performance (e.g., high capacity loading).

[0036] For example, the combination of (i) the continuous volume change of high-capacity nanocomposite particles during cycling and (ii) the decomposition of the electrolyte at the electrically conductive electrode surface at the electrode operating potential (e.g., in the case of Si-based anodes, mainly electrochemical electrolyte reduction) can result in the continuous (albeit relatively slow) growth of a solid electrolyte interphase (SEI) layer at the surface of the nanocomposite particles, resulting in irreversible loss of cell capacity.

[0037] Binder swelling in electrolytes may depend not only on the binder composition but also on the electrolyte composition. Moreover, such swelling (and the resulting performance degradation) often correlates with the decrease in the binder's modulus upon exposure to electrolyte. In this sense, the smaller the decrease in modulus in a particular electrolyte, the more stable the binder-linked (nano)composite active particle / conductive additive interface. A decrease in binder modulus of more than 15-20% may lead to a significant decrease in performance. In one example, a two-fold (2x) decrease in binder modulus may lead to substantial performance degradation. In a further example, a five-fold or more (e.g., 5x-500x) decrease in modulus may lead to very significant performance degradation. Thus, selecting an electrolyte composition that does not induce significant binder swelling may be highly preferred in certain applications. In some examples, it may be preferable to select an electrolyte composition that reduces the binder modulus by less than about 30 vol.% (more preferably, 10 vol.% or less) when exposed to electrolyte. For anodes that include two or more binder compositions, it may be preferable to select an electrolyte composition in which the modulus of at least one binder does not decrease by more than 30 vol.% (more preferably, by more than 10 vol.%) when exposed to the electrolyte.

[0038] The following electrolyte compositions have consistent volume changes during cycling (moderately high volume changes (e.g., about 8 to about 160 or about 180 vol.% increase or about 8 to about 70 vol.% decrease) during the first charge-discharge cycle, and moderate volume changes (e.g., about 4 to about 50 vol.%) during subsequent charge-discharge cycles), average sizes in the range of about 0.2 to about 40 microns (more preferably, about 0.4 to about 20 microns for some applications), and average sizes of about 0.5 microns.2 / g ~ about 50 m 2These electrolytes may be useful for use in Li and Li-ion cells that contain high capacity nanocomposite electrode powders (including conversion or alloy type active materials) that produce specific surface areas in the range of 1000 μg / g. These electrolytes may contain one or more of the following components: (a) a low melting point (LMP) solvent or solvent mixture; (b) a normal melting point (RMP) solvent or solvent mixture; (c) an additive (ADD) solvent or solvent mixture (e.g., added to improve anode electrolyte interphase properties, or improve cathode electrolyte interphase properties, or stabilize Li salts, or provide other useful functionality); (d) a main (MN) Li salt or Li salt mixture; (e) an additive (ADD) salt or salt mixture (not necessarily Li-based) (e.g., added to improve anode electrolyte interphase properties, or improve cathode electrolyte interphase properties, or stabilize Li salts, or provide other useful functionality); (f) other functional additives (OFADD) (e.g., added to enhance cell safety). The LMP solvent or LMP solvent mixture preferably comprises about 10 to about 95 vol.% of the total solvent volume in the electrolyte (more preferably, in some designs, the LMP solvent or LMP solvent mixture may comprise about 10 to about 80 vol.% of the total solvent volume in the electrolyte; e.g., for cells including high capacity nanostructured anodes, a more preferred volume fraction of the LMP solvent may range from about 20 vol.% to about 60 vol.%), the RMP solvent or RMP solvent mixture preferably comprises about 5 to about 90 vol.% of the total solvent volume in the electrolyte (more preferably, in some designs, the RMP solvent or RMP solvent mixture may comprise about 20 to about 90 vol.% of the total solvent volume in the electrolyte), and the ADD solvent or solvent mixture preferably comprises about 0 to about 6 vol.% of the total solvent volume in the electrolyte. The particular values ​​of the optimal volume fractions of the LMP, RMP and ADD solvent or solvent mixture for a particular application may depend on the cell operating potential, cell operating (or cell storage) temperature, and charge and discharge rates desired for the cell in a given application.Examples of esters suitable for use as LMP solvents or co-solvents include various formate esters (e.g., methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, hexyl formate, heptyl formate, etc.), various acetate esters (e.g., methyl acetate, ethyl acetate, propyl acetate, butyl acetate, amyl acetate, hexyl acetate, heptyl acetate, etc.), various propionate esters (e.g., methyl propionate, ethyl propionate, propionate, etc.), to name a few. butyl propionate, amyl propionate, hexyl propionate, heptyl propionate, etc.), various butyrate esters (methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, amyl butyrate, hexyl butyrate, heptyl butyrate, etc.), various valerate esters (e.g., methyl valerate, ethyl valerate, propyl valerate, butyl valerate, amyl valerate, hexyl valerate, heptyl valerate, etc.), various caproate esters (e.g., methyl caproate, ethyl caproate, propyl caproate, butyl caproate, amyl caproate, hexyl caproate, heptyl caproate, etc.), various heptanoate esters (e.g., methyl heptanoate, ethyl heptanoate, propyl heptanoate, butyl heptanoate, amyl heptanoate, hexyl heptanoate, heptyl heptanoate, etc.), various caprylate esters (e.g., methyl caprylate, ethyl caprylate, propyl caprylate, butyl caprylate, amyl caprylate, hexyl caprylate, heptyl caprylate, etc.), various nonanoate esters (e.g., methyl nonanoate, ethyl nonanoate, propyl nonanoate, butyl nonanoate, amyl nonanoate, hexyl nonanoate, heptyl nonanoate, etc.), various decanoate esters (e.g., methyl decanoate, ethyl decanoate, propyl decanoate, butyl decanoate, amyl decanoate, hexyl decanoate, heptyl decanoate, etc.), and fluorinated versions of the esters discussed above.Examples of solvents suitable for use as the RMP solvent in the electrolyte (or for making a mixture of RMP solvents in the electrolyte) include various carbonates (fluorinated acyclic carbonates and propylene carbonate may be particularly advantageous for use in cells containing high voltage cathodes), various sulfones (e.g., dimethyl sulfone, ethyl methyl sulfone, etc.), and various sulfoxides, various lactones, various phosphorus-based solvents (e.g., dimethyl methyl phosphonate, triphenyl phosphonate, etc.), various silicon-based solvents, various types of high melting point esters (e.g., The RMP solvents may include esters having a melting point above about minus (-) 50°C), various ethers (such as dioxolanes, monoglymes, diglymes, triglymes, tetraglymes, and polyethylene oxides), various cyclic ester-based molecules (such as butyrolactone and valerolactone), various dinitriles (such as succinonitrile, adiponitrile, and glutaronitrile), and various ionic liquids (such as imidazoliums, pyrrolidiniums, piperidiniums, and the like, which may be particularly useful in cells containing high voltage cathodes). RMP solvents may also be fluorinated (either fully or partially). The most widely used fluorinated solvent (in Li-ion batteries) is fluoroethylene carbonate (FEC). Although FEC helps to form a more stable (more cross-linked compared to ethylene carbonate, EC) SEI, its use in excess (e.g., greater than about 30 vol.%) can also lead to a decrease in cell performance, especially in cells with high voltage cathodes operating at high temperatures or / and greater than about 4.2 V vs. Li / Li+. Examples of solvents suitable for use as ADD solvents in the electrolyte (or for making ADD solvent mixtures in the electrolyte) can include, among others, various carbonates (including fluorocarbonates), various sulfones (including fluorinated), various sulfoxides (including fluorinated), various lactones (including fluorinated), various phosphorus-based solvents (including fluorinated), various silicon-based solvents (including fluorinated), and various ethers (including fluorinated), various nitriles and dinitriles.Nitriles and dinitriles typically suffer from undesirable SEI formation in the anode, but in small amounts (e.g., typically less than 10 vol.%, more typically less than 5 vol.%), their application in the electrolyte mixture can improve electrolyte conductivity and cell performance, especially when high voltage cathodes are utilized. In some cases (e.g., when high (e.g., greater than about 20 vol.%) contents of so-called "SEI formers" are utilized in the electrolyte), nitriles and dinitriles can also be components of the LMP solvent mixture.

[0039] As used herein, LMP refers to a melting point (of a solvent or solvent mixture) that is generally below a threshold value (e.g., below minus (-) 60°C), typically in the range of, for example, about minus (-) 120°C to about minus (-) 60°C. As used herein, RMP refers to a melting point (of a solvent or solvent mixture) that is generally above a threshold value (e.g., above minus (-) 60°C), typically in the range of, for example, about minus (-) 60°C to about plus (+) 30°C. In further examples, LMP may refer to a melting point (of a solvent or solvent mixture) in a narrower range, for example, in the range of about minus (-) 110°C to about minus (-) 70°C, or about minus (-) 100°C to about minus (-) 80°C.

[0040] In one or more embodiments of the present disclosure, it may be further advantageous for the LMP solvent (or at least one major component of the LMP solvent mixture) in the electrolyte to exhibit a boiling point greater than about +50° C. (more preferably, greater than about +70° C., and even more preferably, greater than about +80° C.).

[0041] Further discussion is provided below regarding cells containing the same types of high capacity nanocomposite electrode particles or powders as described above (e.g., containing the same type / class of high capacity nanocomposite anode powder in the anode, or containing the same type / class of high capacity nanocomposite cathode powder).

[0042] In some designs, various cyclic or linear esters (e.g., γ-valerolactone, γ-methylene-γ-butyrolactone, γ-hexalactone, α-angelicalactone, α-methylene-γ-butyrolactone, ε-caprolactone, 5,6-dihydro-2H-pyran-2-one, γ-butyrolactone, δ-hexalactone, α-methyl-γ-butyrolactone, phthalide, γ-caprolactone, propyl acetate, methyl formate, ethyl acetate, propyl propionate, methyl propionate, ethyl propionate, methyl valerate, etc.) were used. butyl, methyl butyrate, ethyl butyrate, butyl valerate, butyl butyrate, etc.) (some designs contain no functional groups, some designs contain additional functional groups (e.g., halogens, alcohols, alkanes, alkenes, alkynes, ketones, aldehydes, ethers, amines, amides, imides, nitriles, sulfonyls, carboxylic acids, phosphates, etc.)), various cyclic or linear ethers (e.g., tetrahydrofuran, tetrahydropyran, furan, 4-methylpyran, pyran, 12-crown-4, 15-crown-5, 18-crown-6, 19-crown-7, 20-crown-8, 21-crown-9, 22-crown-10, 23-crown-11, 24-crown-12, 25-crown-13, 26-crown-14, 27-crown-15, 28-crown-16, 29-crown-17, 30-crown-18, 31-crown-19, 32-crown-19, 33-crown-16, 34-crown-17, 35-crown-18, 36-crown-19, 37-crown-19, 38-crown-19, 39-crown-20, 32-crown-21, 39-crown-22, 39-crown-23, 39-crown-24, 39-crown-25, 38-crown-26, 39-crown-27, 39-crown-28, 39-crown-29, 40-crown-29, 40-crown-29, 40-crown-29, 4 -crown-6, 4-methyl-1,3-dioxane, dimethyl ether, methyl t-butyl ether, diethyl ether, methoxyethane, dioxane, dioxalane, monoglyme, diglyme, triglyme, tetraglyme, etc. (some designs contain no functional groups, some designs contain additional functional groups (e.g., halogens, alcohols, alkanes, alkenes, alkynes, ketones, aldehydes, ethers, amines, amides, imides, nitriles, sulfonyls, carboxylic acids, phosphates, etc.)), various anhydrides (e.g., For example, glutaric anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, cyclobutane-1,2,3,4-tetracarboxylic dianhydride, butyric anhydride, isobutyric anhydride, etc. (some designs containing no functional groups, some designs containing additional functional groups (e.g., halogens, alcohols, alkanes, alkenes, alkynes, ketones, aldehydes, ethers, amines, amides, imides, nitriles, sulfonyls, carboxylic acids, phosphates, etc.) may be advantageously utilized as LMP solvents or co-solvents in LMP mixtures.

[0043] In some designs, the addition of various functional groups to the selected electrolyte solvent (e.g., to at least a portion of the solvents in the LMP or LMP mixture, e.g., anhydrides, ethers, esters, and others, or to at least a portion of the solvents from the RMP or RMP mixture) may provide various advantages in certain applications. For example, the addition of electron donating materials (e.g., alkanes, methoxys, amines, etc.) may reduce the reduction potential (i.e., make it less susceptible to reduction), which may be advantageous when such reduction needs to be avoided or minimized for a particular solvent (e.g., when such a solvent is not used to form an SEI, but is added to maintain high ionic conductivity in the electrode pores at cell operating temperatures). In another example, the addition of electron withdrawing materials (e.g., fluorines, esters, nitro groups, etc.) may increase the solvent reduction potential (make it more susceptible to reduction), which may be advantageous when such a solvent is used as a component of a stable SEI formation. In one example, the formation of such an SEI at high potentials (before other electrolyte solvent components are reduced) may prevent undesired reduction of other solvents at the electrode surface (e.g., solvents that form less stable SEIs, or SEIs with less ionically conductive, or other less favorable characteristics). Furthermore, such solvents may present a higher oxidation potential (which may be advantageous for maintaining improved stability, reducing leakage rates, etc.) when the cathode is exposed to high electrode potentials (e.g., above about 4.4 V vs. Li / Li+).

[0044] In the case of electron-withdrawing materials, the replacement of selected hydrogen atoms in such solvents or co-solvents with fluorine atoms (e.g., by using various fluorination reactions or other mechanisms) may be particularly advantageous in some designs. In particular, electrolyte solvents / co-solvents (e.g., components of LMPs and / or RMP electrolyte solvent components) that already work sufficiently well when applied (e.g., form some stable SEI) may further benefit from at least partial fluorination (e.g., exhibit increased cycling stability or other benefits), especially when high capacity nanostructured anodes (e.g., Si-containing anodes) are utilized in cell construction. Such reactions may increase the likelihood of SEI formation and enhance the electrochemical stability of the electrodes during cycling (e.g., via enhanced stability of the anode SEI or cathode SEI protective layer). Suitable examples include various fluorinated esters, various fluorinated ethers, various fluorinated anhydrides in the case of LMP components, and various other fluorinated solvents (including carbonates, nitriles, sulfones, larger esters, etc.) in the case of RMP components. It should be recognized that the optimal fluorinated or fluorinated solvent content may vary depending on the application. For example, the use of an excessive amount of fluorinated or too much fluorinated solvent may be undesirable in some applications (e.g., when the battery cathode may be exposed to high temperatures (e.g., above about 40° C.) and high operating potentials (e.g., above 4.4 V vs. Li / Li+). Furthermore, the use of an excessive amount of fluorinated or too much fluorinated solvent may reduce electrolyte wetting of the separator or part of the electrode, thus reducing capacity utilization and rate performance, especially at low temperatures. The optimal content of fluorinated solvent may depend on the cell operation and the surface chemistry and properties of the electrode and separator.

[0045] In some designs, the use of solvents (co-solvents) (e.g., components of LMPs or RMP electrolyte solvent components) that exhibit double bonds in their structure (e.g., one, less than one, or more than one double bond per solvent molecule), or other opportunities to form polymers upon chemical or electrochemical reactions, may be advantageous for the formation of a more stable SEI (e.g., via alkene polymerization). Solvent molecules that contain both double bonds and fluorine may be particularly attractive for the formation of SEIs with favorable characteristics (e.g., improved stability, etc.). Similarly, solvents (co-solvents) that can undergo ring-opening polymerization (e.g., solvents with alkenes or various heteroatom-containing ring structures, e.g., propanesulfone) may also be advantageously utilized as electrolyte components in some designs due to their ability to form more stable SEIs.

[0046] The polarity of the solvent (co-solvent), which is influenced by functional groups, can have a large effect on the electrolyte properties. For example, more polar solvents can provide higher solubility for electrolyte salts and thus contribute to improved ionic conductivity. At the same time, more polar solvents are typically less likely to dry (making it costly to remove water residues). Furthermore, many polar solvents (such as amines and alcohols) can also be sources of protons, which can lead to undesirable side reactions (such as hydrogen evolution).

[0047] In some designs, it may be beneficial to have a mixture of solvents in the electrolyte (at least in combination with an electrolyte salt) where one or more of them exhibit a wide electrochemical stability window and one or more of them exhibit a narrower electrochemical stability window. In some designs, it may be beneficial for the difference in electrochemical stability windows of at least some of the electrolyte solvents to be greater than about 1 V. In some designs, it may be advantageous for at least one component of the LMP solvent mixture to exhibit a higher electrochemical stability window (at least when used with the same electrolyte salt) than at least one component of the RMP solvent mixture.

[0048] FIG. 2 shows examples of linear ester solvents (containing no additional functional groups) selected for their melting points and other characteristics (e.g., boiling point, flash point, refractive index) that can be effectively used as the LMP (or RMP) component of suitable electrolyte compositions according to embodiments of the present disclosure.

[0049] Figures 3A and 3B show illustrative examples of selected performance characteristics of a matched full cell containing an intercalated lithium iron phosphate (LFP) powder cathode and a high capacity nanocomposite Si-containing powder anode. The cell was cycled at potentials ranging from 1.85 to 3.65 V. The nanocomposite anode exhibited moderate to high volume change during the first charge-discharge cycle and moderate volume change during subsequent charge-discharge cycles. Individual anode particles had an average particle size of about 3 microns and a mass distribution of about 5 m. 2 The anode coating contained 92 wt.% nanocomposite anode powder and 8 wt.% inactive components (binder and conductive additives). The cell electrolyte contained 2 vol.% vinylene carbonate (VC) (as the ADD electrolyte component), 40 vol.% mixture of cyclic and linear carbonates (20 vol.% each) (as the RMP component of the electrolyte), and a very high content (as high as 58 vol.%) of methyl butyrate (MB) (as the linear ester and LMP component of the electrolyte; methyl butyrate exhibits a very low melting point of about -95 °C). The cycling stability is illustrated by the specific capacity of the anode active material. Figure 3A shows typical charge-discharge curves for cycle 1 (curve of higher charge capacity) and cycle 5 (curve of lower charge capacity due to irreversible losses in the first cycle). This example cell exhibited a first charge-discharge cycle efficiency of 88%. 3B shows the electrochemical stability of an example cell, with specific capacity normalized by the weight of the active anode material (weight of the anode coating of 92 wt.%). The cell was cycled at room temperature at a 0.5° C. rate and exhibited a cycle life of about 940 cycles (to 80% of capacity at cycle 5).

[0050] While some designs utilize a mixture of two or more salts, it may be advantageous to have a total salt concentration in the electrolyte in the range of about 0.8 M to about 2.0 M. Salt concentrations in the electrolyte below about 0.8 M can be problematic, especially when high area capacity electrodes are used (e.g., about 4 mAh / cm2). 2 ) (e.g., when high capacity anode materials are used) can result in reduced cell stability. Higher salt concentrations in the electrolyte can result in reduced rate performance and, in some designs, reduced cell stability. Such reduced performance characteristics can be attributed to the presence of Li in the electrolyte. + This may be related to the reduced mobility of cations. Higher salt concentrations may also result in increased electrolyte density and cost, which may not be desirable in some applications. The optimal salt concentration may depend on the specific cell design and electrolyte composition. Interestingly, some cells (e.g., those that contain Li2S or Li2Se or S or Se-based conversion cathodes or Li metal anodes, among others) may sometimes benefit from reduced electrolyte molarity (e.g., less than about 0.2M) (e.g., when fast charging is not required).

[0051] In some cases, salt combinations may have higher Li than the individual salts at the same concentration. + In some designs, such salts may be selected such that the Li salts (or their solvated counterparts) form eutectic systems (with depressed melting points). In one example, some Li imide salts (e.g., SOFN - (Li + )SO2F and CF3SO2N - (Li + )SO2CF3 salt mixture, or CF3SO2N - (Li + )SO2CF3 and CF3CF2SO2N - (Li + )SO2CF3 mixture, or CF3SO2N - (Li + )SO2CF3 and CF3CF2SO2N - (Li +)SO2CF2CF3) may form such a system. In some designs, such salts and their relative fractions may be selected to induce freezing point depression. In some designs, the most preferred relative fractions of salts may be selected to minimize the freezing point (through such freezing point depression). In some designs, other Li and non-Li salts may be added in small amounts (e.g., about 0.001M to about 0.500M) to further depress the electrolyte melting point, improve SEI properties, and reduce dissolution of the active materials or their components. In some designs, the non-Li salts may be salts of Mg, K, Ca, or Na. In some designs, the non-Li salts may be salts of rare earth metals (e.g., La).

[0052] In some designs utilizing two or more salts (e.g., three salts, or four salts, or five salts, etc.), it may be advantageous for at least one of the salts to comprise LiPF6 (for rechargeable Li or Li-ion batteries). In some designs, it may be even more advantageous for one other salt to also be a salt of Li. It may be even more advantageous for at least one other (non-LiPF6) salt to be electrochemically unstable in the electrolyte (e.g., decompose at the anode) upon a drop in anode potential below about 0.3-2.3 V vs. Li / Li+. In some designs, it may be advantageous for the salt to decompose above about 0.3 V vs. Li / Li+, more preferably above about 1 V vs. Li / Li+ (and in some designs, more preferably above about 1.5 V vs. Li / Li+). It may be further advantageous for the non-LiPF6 salt in the electrolyte to induce or catalyze electrolyte reduction at greater than about 0.3 V vs. Li / Li+, more preferably greater than about 1 V vs. Li / Li+ (and in some designs, more preferably greater than about 1.5 V vs. Li / Li+ or even greater than about 2.0 V vs. Li / Li+). It may be further advantageous for the (e.g., partially decomposed) non-LiPF6 salt in the electrolyte to react with at least a portion of the solvent molecules in the electrolyte to form oligomers. In some designs, the non-LiPF6 salt may be a LiFSI salt. Furthermore, for electrolytes containing both LiPF6 and LiFSI salts, the ratio of the mole fractions of LiPF6 and LiFSI salts may preferably range from about 100:1 to about 1:1. The exact optimal ratio may depend on the electrode features (e.g., thickness, amount of binder, density, anode and cathode composition, and capacity, etc.), the electrolyte solvent mixture utilized, and the cycle operating conditions (temperature, cell voltage range, etc.). It may further be advantageous for the electrolyte solvent to include a mixture of LMP and RMP solvents, and (optionally) ADD and other co-solvents. In some designs, it may also be advantageous for the LMP solvent or solvent mixture to include esters.

[0053] In some designs, it may be advantageous to utilize a small fraction of at least one at least partially fluorinated solvent in the electrolyte mixture, ranging from about 1 to about 30 vol.% as a fraction of all solvents in the electrolyte, while having a total salt concentration in the electrolyte ranging from about 0.8 M to about 2.0 M. It may be further advantageous for the electrolyte solvent mixture to include both linear and cyclic molecules. It may be advantageous for at least one of the cyclic molecules to include a fluorine atom. In some designs, it may be preferred for the electrolyte to include a fluoroethylene carbonate (FEC) co-solvent in the electrolyte (e.g., ranging from about 1 to about 30 vol.% as a fraction of all solvents in the electrolyte). In one example, the optimal amount of FEC may depend on the surface area of ​​the nanostructured anode particles. Smaller surface areas (e.g., about 15 m 2 For nanostructured anode particles having a surface area (e.g., less than about 15 m / g), the FEC content may not significantly affect the formation efficiency. 2For particles exhibiting a 100% FEC content (>100% / g), a higher FEC content may allow for improved formation efficiency. Smaller surface areas and smaller volume changes may also require smaller FEC fractions for stable operation. Higher FEC contents (e.g., greater than 20-30 vol.%) may degrade cell performance at high temperatures (e.g., greater than about 35°C), especially when the cell cathode is exposed to high potentials (e.g., greater than about 4.3-4.4 V vs. Li / Li+). It may further be advantageous for the electrolyte solvent to include a mixture of LMP and RMP solvents, and (optionally) an ADD solvent. In some designs, it may also be advantageous for the LMP solvent or solvent mixture to include an ester. In some designs, it may also be advantageous for the electrolyte to include other cyclic carbonates (or other fluorinated cyclic carbonates) in addition to FEC. In some designs, it may be advantageous for the other cyclic carbonate to include ethylene carbonate (EC) having a melting point of about +34-37° C. or another cyclic carbonate having a high melting point (e.g., above about +25° C.). Additionally, the vol. ratio of FEC (or other fluorinated cyclic carbonate) to the other cyclic carbonate may preferably range from about 9:1 to about 1:50. The exact optimum ratio may depend on the electrode features (e.g., thickness, amount of binder, density, anode and cathode composition, and capacity, etc.), the electrolyte solvent mixture utilized, and the cycling operating conditions of the cell (temperature, voltage range, etc.).

[0054] Figures 4A and 4B illustrate the effect of several example electrolyte compositions on the performance of cells containing a powder-based high capacity Si-containing nanocomposite anode and a powder-based intercalated cathode (in this example, lithium cobalt oxide, LiCO) cycled over a voltage range of 2.5 to 4.4 V. Cycling stability was tested for several example cells cycled at a "C / 2" rate. Two to three nearly identical cells were constructed and tested for consistency. In these examples, all electrolytes contain the same salt (LiPF6) in an amount of 1.2 M, an ester (having a melting point below -90°C) selected from Figures 2-a, 2-b in an amount of 58 vol.% (as a fraction of the total solvent volume) in an amount of 2 vol.%, the same ADD cyclic carbonate solvent in an amount of 20 vol.%, the same linear carbonate in an amount of 20 vol.%, and various amounts of FEC (ranging from 0 to 30 vol.%) and another cyclic carbonate (EC) (ranging from 0 to 30 vol.%), so that the total amount of cyclic carbonate is kept constant at 30 vol.%. Figure 4A illustrates that nanostructured Si anodes with larger surface areas show lower first charge-discharge cycle efficiencies (e.g., data points corresponding to the lower curve in Figure 4A) and a stronger dependence of efficiency on FEC fraction. The smaller surface area of ​​the nanostructured Si anode shows higher first charge-discharge cycle efficiency (e.g., data points corresponding to the upper curve in FIG. 4A) and weaker dependence of efficiency on FEC fraction. FIG. 4B shows the performance of Li-ion cells containing Si-containing anodes at room temperature and 45° C., illustrating that for nearly identical cells containing nearly identical Si-containing anodes, an FEC content (in this example) of less than about 20 vol.% reduces cell cycling stability at room temperature (e.g., data points corresponding to the upper curve in FIG. 4B), while an FEC content of more than about 20 vol.% reduces stability slightly at 45° C. (e.g., data points corresponding to the lower curve in FIG. 4B).

[0055] The area electrode capacity is about 4mAh / cm 2In some designs higher than 1M, it may be advantageous to have a total Li salt concentration in the electrolyte greater than about 1M (preferably greater than about 1.1M, and in some designs greater than about 1.2M and less than about 2.4M, and in some designs less than about 1.8M) when utilizing at least one at least partially fluorinated solvent in the electrolyte in a small fraction ranging from about 1 vol.% to about 30 vol.% as a fraction of all solvents in the electrolyte. At such high capacity loadings, Li salt concentrations of 1 to 1.1M or less may result in faster decomposition in some designs, especially when high capacity Si-containing composite anodes are used.

[0056] Figure 5 illustrates the effect of salt concentration on the performance of low and high electrode capacity loading cells containing a powder-based high capacity Si-containing nanocomposite anode and a powder-based intercalated cathode (in this example, lithium cobalt oxide, LiCO) cycled in the voltage range of 2.5 to 4.4 V. Cycling stability was tested on several example cells cycled at a "C / 2" rate. Two nearly identical cells were constructed and tested for consistency. In these examples, all electrolytes contain LiPF6 salt in amounts of either 1 M or 1.2 M, FEC 20 vol.%, DEC 78 vol.% and VC 2 vol.%. As is evident from the results shown in Figure 5, the high capacity loading (in this example, 5.7 mg / cm) of the cells exhibited excellent performance. 2 The poor cycling stability of the cell containing the anode with a high mass loading of 10 ... 2 ), the beneficial effect of higher salt concentrations becomes significantly smaller (e.g., in Figure 5, 1.2 M LiPF 2 The curve for 1.2M LiPF65.7 mg / cm 2 (compare with ).

[0057] In some designs, it may be advantageous to utilize a small fraction of fluorine-containing cyclic carbonates (e.g., fluoroethylene carbonate (FEC)) as a co-solvent in the electrolyte (e.g., in the range of about 1 to about 30 vol.% as a fraction of all solvents in the electrolyte), other (e.g., fluorine-free) cyclic carbonates and linear (e.g., fluorine-containing or fluorine-free) carbonates with melting points in the range of about minus (-) 10°C to about minus (-) 60°C), while having a total salt concentration in the electrolyte in the range of about 0.8M to about 2.0M. It may be advantageous for the carbonates (e.g., cyclic carbonates) to include a double-bonded oxygen (=O, a carbonyl group) in their molecular structure. It may also be advantageous for the carbonates (e.g., cyclic carbonates) to include at least one methyl side group (-CH3) in their molecular structure. In some designs, it may also be advantageous for propylene carbonate (PC), which has a melting point of about minus (-) 49°C, to be at least one of the cyclic carbonates in the electrolyte mixture. The amount of PC may preferably range from about 0 to about 50 vol.%. In some designs, an amount of PC ranging from about 25 vol.% to about 50 vol.% may be advantageous. This is in contrast to conventional graphite anode-containing cells, which typically show a significant decrease in stability when the amount of PC exceeds 5 to 20 vol.%. It may also be advantageous for the electrolyte to include a mixture of 2 to 5 cyclic carbonates with different melting points in addition to FEC, or in addition to the FEC and PC mixture. It may further be advantageous for the electrolyte solvent to include a mixture of LMP and RMP solvents, and (optionally) ADD and solvent. In some designs, it may also be advantageous for the LMP solvent or solvent mixture to include an ester. In some designs, it may be advantageous for the ADD solvent to include a small amount (e.g., about 0.1 to about 5 vol.%) of vinylene carbonate (VC) or vinylethylene carbonate (VEC) cyclic carbonate (the use of VC may be preferred in some designs). It may be more advantageous for the total amount of all cyclic solvents in the electrolyte mixture to be in the range of about 10 to about 60 vol.%. It may be more advantageous for the total amount of cyclic carbonates in the electrolyte mixture to be in the range of about 10 to about 50 vol.%.Higher amounts of cyclic solvents are generally detrimental to capacity retention at high cycling C-rates or performance at low temperatures, and in some cases also to cycling stability.

[0058] In some designs, it may be advantageous to utilize a small fraction of fluoroethylene carbonate (FEC) co-solvents in the electrolyte (e.g., in the range of about 1 to about 30 vol.% as a fraction of all solvents in the electrolyte), some amount of non-FEC cyclic carbonates (e.g., in the range of about 5 to about 30 vol.% as a fraction of all solvents in the electrolyte), and some amount of LMP co-solvents (e.g., in the range of about 20 to about 70 vol.% as a volume fraction of all solvents in the electrolyte), while having a total salt concentration in the electrolyte in the range of about 0.8 M to about 2.0 M. In some designs, it may be advantageous for the electrolyte composition to further include at least one linear solvent (e.g., as a component of an LMP or RMP solvent or solvent mixture). In some designs, it may be advantageous for the electrolyte composition to include at least one linear carbonate (e.g., as a component of an RMP solvent mixture). In some designs, it may be advantageous for the electrolyte to include a mixture of two or more linear carbonates. In some designs, it may be advantageous for the fraction of linear carbonate to comprise about 5 vol.% to about 60 vol.% (as a volume fraction of all solvents in the electrolyte). In some designs, it may be even more advantageous for the total fraction of all linear carbonates to comprise about 10 vol.% to about 30 vol.% (as a volume fraction of all solvents in the electrolyte). In some designs, it may be preferred that at least one of the linear carbonates or the only linear carbonate or a mixture of all linear carbonates in the electrolyte exhibits a melting point of about -10°C to about -60°C. In one example, the size of the linear carbonate molecule may play a large role in cell performance. For example, shorter linear carbonates in the electrolyte may lead to better rate performance and in some cases better cycling stability. However, linear carbonates that are too short may also result in reduced cycling stability. In some designs, the average number of linear carbonate atoms in the electrolyte may preferably range from about 12 to about 26 per carbonate molecule. In some designs, it may be advantageous for the electrolyte to include diethyl carbonate (DEC) as a component of the linear carbonate or linear carbonate mixture.DEC-containing electrolytes may exhibit better rate performance (e.g., better capacity retention at higher rates). Additionally, electrolytes containing DEC may exhibit high cycling stability in certain applications.

[0059] FIG. 6 illustrates the effect of example electrolyte compositions on the performance of cells containing a powder-based high capacity Si-containing nanocomposite anode and a powder-based intercalated cathode (in this example, lithium cobalt oxide, LiCO) cycled over a voltage range of 2.5 to 4.4 V. Cycling stability was tested on several example cells cycled at 45° C. at a “C / 2” rate. Two to three nearly identical cells were constructed for each electrolyte composition and tested for consistency. Electrolyte B (upper curve in FIG. 6) contains 1 M LiPF6, 0.2 M LiFSI, 20 vol.% PC, 10 vol.% FEC, 20 vol.% linear carbonate (in this example, DEC), 2 vol.% VC, and 48 vol.% linear ester (MB). Electrolyte A (lower curve in FIG. 6), containing 1.2 M LiPF6, no LiFSI, 20 vol. % FEC and the same linear ester (MB), shows reduced cycling stability.

[0060] In some designs, it may be advantageous for the LMP solvent in a suitable electrolyte composition to exhibit a particular molecular size for optimal performance. The optimal size or size distribution of the LMP molecules may depend on the electrode features (e.g., thickness, amount of binder, density, anode and cathode compositions, and capacity, etc.), the electrolyte solvent mixture utilized, and the cycling operating conditions of the cell (temperature, voltage range, etc.). In one example, the average LMP molecule (e.g., in an LMP solvent mixture, if two or more LMP solvents are utilized, or in a single-solvent LMP composition) may preferably contain from about 9 atoms to about 30 atoms per solvent molecule. In some designs, it may be advantageous for the average LMP molecule (e.g., in an LMP solvent mixture or in a single-solvent LMP composition) to contain from about 3 to about 10 carbon atoms in its molecular structure. Smaller LMP molecules (especially smaller linear molecules) may lead to reduced cell cycling stability. Larger LMP molecules (especially larger linear molecules) may lead to undesirable reduced cell rate performance. When linear esters are used as components of the LMP solvent, it may be advantageous for such esters to contain, on average, about 3 to about 9 carbon atoms per molecule. When the LMP solvent includes esters with side branches (additional functional groups), it may be advantageous for such esters to contain, on average, about 4 to about 12 carbon atoms per molecule. In some designs, an average ester molecule (in the LMP co-solvent) containing, on average, 4 to 7 carbon atoms per molecule may provide the most stable performance in the cell. In some designs, an average ester molecule (in the LMP co-solvent) containing, on average, 5 to 6 carbon atoms per molecule (in some designs, 5 carbon atoms per molecule) may provide the most stable performance in the cell. In some designs, it may be advantageous for about 50 vol.% or more of the LMP solvent to include ester molecules containing, on average, 5 atoms per molecule.

[0061] 7A to 7C illustrate the effect of other example electrolyte compositions on the performance of cells containing a powder-based high-capacity Si-containing nanocomposite anode and a powder-based intercalated cathode (lithium cobalt oxide, LCO in this example) cycled in the voltage range of 2.5 to 4.4 V. Cycling stability was tested on several example cells cycled at room temperature and 45° C. at “C / 2” rate. Two to three nearly identical cells were constructed and tested for consistency. In these examples, all electrolytes contain 1.2 M LiPF6, 20 vol.% FEC, 20 vol.% linear carbonate, 2 vol.% cyclic carbonate (VC in this example) as ADD solvent, and 48 vol.% linear ester. Esters of different molecular size (and molecular weight) were selected for each electrolyte, as shown in each figure. In this illustrative example, only one type of ester (not a mixture of esters) was used in each electrolyte. The rate performance of cells containing this series of electrolytes was strongly correlated to the carbon chain length of the ester. Cells based on electrolytes with the shortest carbon chain length in the ester showed the best capacity retention at higher rates, while cells containing electrolytes with the longest carbon chain length in the ester showed the worst capacity retention. In this example, esters containing six or more carbon atoms in the molecule showed an undesirable decrease in performance. Electrolytes containing esters with 5-6 carbon atoms per molecule showed the best cycling stability at room temperature. Electrolytes containing esters with 3 carbon atoms per molecule showed very fast decomposition at room temperature and at 45°C. Electrolytes containing esters with 8-9 carbon atoms per molecule showed significantly faster decomposition at room temperature and much faster decomposition at 45°C.

[0062] In some designs where esters are used as co-solvents in the suitable electrolyte mixture (e.g., for some cells with high capacity nanostructured anodes and high voltage intercalating cathodes), it may be advantageous for the total fraction of esters in the electrolyte solvent to range from about 20 vol.% to about 70 vol.% (about 30 vol.% to about 60 vol.% in some designs with only linear esters) as the total vol. fraction of all solvents in the electrolyte. Lower and higher ester fractions may result in a significant decrease in cycling stability, especially at high temperatures.

[0063] In some designs, it may be advantageous (for improved cell performance) to use a combination of two, three or more esters of the same chemical formula but different molecular structures in the electrolyte solvent mixture. For example, methyl butyrate (CH 10 O2) to ethyl propionate (C5H 10 O2) or propyl acetate (C5H 10 O2) or butyl formate (CH 10 O2) or various mixtures (or combinations) thereof. Or, in another example, the following esters: methyl valerate (CH 12 O2), Ethyl butyrate (C6H 12 O2), Propyl propionate (C6H 12 O2), Butyl Acetate (CH 12 O2) and amyl formate (CH 12 Or, in yet another example, the following esters are used: methyl caproate (CH 14 O2), Ethyl valerate (C7H 14 O2), Propyl butyrate (C7H 14 O2), Butyl Propionate (C7H 14 O2), amyl acetate (C7H 14 O2), Hexyl Formate (C7H 14 O2) in combination with two, three or more of the above.

[0064] Some designs use, for example, combinations of two, three or more esters (and in some designs combinations of ethers and anhydrides) in the electrolyte, with similar chemical formulas that differ by no more than three carbon atoms (e.g., CH 10 O2, C6H 12 O2 and C7H 14 It may be advantageous (for improved cell performance, e.g., improved rate or improved stability, etc.) to use a combination of esters having a chemical formula of O2. In some designs, it may be advantageous for such a combination of esters (or ethers or anhydrides) to exhibit a lower melting point than each of the individual solvents (e.g., individual esters or individual ethers or individual anhydrides).

[0065] In some designs it may be advantageous (for improved cell performance) to use in the electrolyte a combination of esters (and in some designs a combination of ethers or a combination of anhydrides) with and without functional groups. In some designs it may be advantageous for the linear (or cyclic) portions of such esters (or ethers) to be the same or similar, and thus to differentiate these esters (or ethers) by the presence of (e.g., different) functional groups.

[0066] In some designs, when combinations of linear and cyclic esters (and in some designs combinations of esters and ethers) are used, and when they have functional groups, it may be advantageous (for improved cell performance) for at least a portion of the esters or ethers to remain unfunctionalized.

[0067] In some designs it may be advantageous (for improved cell performance) to use a combination of linear and cyclic esters in the electrolyte.

[0068] In some designs, when a combination of linear and cyclic esters are used, and at least some of them have functional groups, it can be advantageous (for improved cell performance) for at least some of the linear and cyclic esters to have the same functional groups.

[0069] In some designs (when mixtures of different esters are used), it may be advantageous for the linear esters in the electrolyte mixture to either exhibit the same chemical tail (same R group) or belong to the same subclass.

[0070] In some designs it may be advantageous (for improved cell performance) to use a combination of ethers and esters in the electrolyte. In some designs it may be advantageous for the number of carbon atoms in the ester molecules to not exceed the number of carbon atoms in the ether molecules by more than 5 (e.g., having 2 or 3 carbon atoms in the ether molecule and 5 or 6 or 7 carbon atoms in the ester molecule).

[0071] In some designs, it may be advantageous (for improved cell performance) to use a combination of esters, ethers and anhydrides (eg, with and / or without functional groups) in the electrolyte.

[0072] In some designs, when combinations of esters, ethers and anhydrides are used, it may be advantageous for the linear (or cyclic) portions of such esters (or ethers or anhydrides) to be the same or similar, such that the esters (or ethers or anhydrides) are differentiated by the presence of (e.g., different) functional groups.

[0073] In some designs it may be advantageous (for improved cell performance) to use a combination of linear and cyclic anhydrides in the electrolyte.

[0074] In some designs (e.g., with cells containing high voltage cathodes), it may be advantageous (for improved cell performance) to use a sulfone as a component of the RMP solvent. In some designs, it may be advantageous for the sulfone to comprise from about 17 vol.% to about 97 vol.% of all RMP solvents in the electrolyte formulation. In some designs, it may be advantageous for the sulfone to comprise both cyclic and linear (or, more generally, acyclic) sulfones.

[0075] The exemplary nanocomposite particles (e.g., anode or cathode particles) described above can generally be of any shape (e.g., near-spherical, cylindrical, plate-like, randomly shaped, etc.) and of any size. The maximum size of the particles can depend on the rate performance requirements, ion diffusivity into the partially loaded particles, and / or other parameters. For most applications, the particles can be smaller than 10 microns for optimal performance, regardless of the average diffusion distance from between the solid electrolyte phases (e.g., from the surface of the composite particle) to the inner core of the composite.

[0076] Some aspects of this disclosure may also be applicable to conventional intercalating type electrodes, particularly those with medium and high capacity loadings (e.g., 3 mAh / cm 2 For electrodes having a Cr content greater than 100%, the benefits of improved rate performance or improved stability may be obtained.

[0077] In one example, the "size" of a nanocomposite particle may be determined by any of a variety of methods. In one example, the size of an individual particle may refer to the diameter of the particle if the particle is spherical or near-spherical. In another example, the size of an individual particle may refer to the diameter of an isovolume sphere of the particle (e.g., a sphere of the same volumetric size representative of the particle) if the particle is non-spherical (e.g., ellipsoidal, oval, etc.). When the isovolume sphere approach is used, the total pore volume of the particle is maintained in an isovolume sphere of the particle. In yet another example, for irregularly shaped particles (e.g., oval particles), the size of an individual particle may refer to the smallest dimension of the particle (e.g., width) or the length of the particle (e.g., length). Thus, the various particle size ranges described with respect to embodiments of the present disclosure may refer to sizes determined according to any of the methodologies described above based on the shape and / or other characteristics of the respective particles.

[0078] This description is provided to enable any person skilled in the art to make or use embodiments of the invention. However, it should be recognized that the invention is not limited to the specific formulations, method steps, and materials disclosed herein, since various modifications to these embodiments will be readily apparent to those skilled in the art. That is, the general principles defined herein may be applied to other embodiments without departing from the spirit or scope of the invention.

Claims

1. anode particles having an average particle size ranging from about 0.2 microns to about 20 microns and including an active material, 2 ~10mAh / cm 2 an anode electrode having a capacity loading in the range of A cathode electrode; a separator that electrically separates the anode electrode and the cathode electrode; an electrolyte that ionically couples the anode electrode and the cathode electrode; Including, the active material comprises one or more of silicon, germanium, antimony, aluminum, magnesium, zinc, gallium, arsenic, phosphorus, silver, cadmium, indium, tin, lead, bismuth, and alloys thereof; The electrolyte is LiPF 6 and an electrolyte solvent composition, the electrolyte solvent composition comprises: (a) one or more esters; and (b) a normal melting point solvent composition; one or more of said esters have a melting point in the range of about -140°C to about -60°C; the average number of carbon atoms per molecule of said ester(s) ranges from 4 to 7; the normal melting point solvent composition having a melting point in the range of about -60°C to about +30°C; A lithium-ion battery cell, wherein the anode particles have a specific surface area ranging from about 0.5 m 2 / g to about 50 m 2 / g.

2. 10. The lithium ion battery cell of claim 1, wherein the average number of carbon atoms per molecule of said ester(s) ranges from 5 to 6.

3. 10. The lithium ion battery cell of claim 1, wherein the electrolyte does not include an ester having 3 carbon atoms per molecule.

4. 10. The lithium ion battery cell of claim 1, wherein the electrolyte does not include esters having 8 or 9 carbon atoms per molecule.

5. 10. The lithium ion battery cell of claim 1, wherein the one or more esters comprise linear or cyclic esters.

6. 10. The lithium ion battery cell of claim 1, wherein the one or more esters include an ester having side branches.

7. 10. The lithium ion battery cell of claim 1, wherein the one or more esters comprise two or more esters of the same chemical formula but different molecular structures.

8. 10. The lithium-ion battery cell of claim 1, wherein at least one ester of the one or more esters is selected from ethyl propionate, propyl propionate, methyl butyrate, or ethyl butyrate.

9. 2. The lithium ion battery cell of claim 1, wherein the difference in the number of carbon atoms per molecule of one or more of said esters is no more than 3.

10. 10. The lithium-ion battery cell of claim 1, wherein the volume fraction of the one or more esters in the electrolyte solvent composition ranges from about 20 vol. % to about 70 vol. %.

11. 10. The lithium ion battery cell of claim 1, wherein the normal melting point solvent composition comprises a fluorinated cyclic carbonate.

12. 12. The lithium ion battery cell of claim 11, wherein the fluorinated cyclic carbonate is fluoroethylene carbonate (FEC), and the volume fraction of FEC in the electrolyte solvent composition ranges from 1 to 30 vol. %.

13. 10. The lithium ion battery cell of claim 1, wherein the normal melting point solvent composition comprises one or more cyclic carbonates.

14. 14. The lithium ion battery cell of claim 13, wherein the one or more cyclic carbonates comprise vinylene carbonate (VC) and / or vinyl ethylene carbonate (VEC), and the volume fraction of the VC and / or VEC in the electrolyte solvent composition ranges from about 0.1 to about 5 vol. %.

15. 14. The lithium ion battery cell of claim 13, wherein the one or more cyclic carbonates are propylene carbonate (PC) and / or ethylene carbonate (EC).

16. 2. The lithium ion battery cell of claim 1, wherein the normal melting point solvent composition comprises one or more linear carbonates, and the volume fraction of the one or more linear carbonates in the electrolyte solvent composition ranges from 5 vol. % to 60 vol. %.

17. 17. The lithium ion battery cell of claim 16, wherein the average number of total atoms per molecule of the one or more linear carbonates is in the range of 12 to 16.

18. 17. The lithium ion battery cell of claim 16, wherein the one or more linear carbonates include a carbonate having 18 atoms per molecule, the carbonate being diethyl carbonate (DEC).

19. 10. The lithium ion battery cell of claim 1, wherein the electrolyte solvent composition comprises nitriles and / or dinitriles at a volume fraction of less than 5 vol. % of the electrolyte solvent composition.

20. 2. The lithium-ion battery cell of claim 1, wherein the total salt concentration in the electrolyte is in the range of about 1.2M to about 1.8M.

21. The electrolyte further comprises SO 2 F.N. - (Li + ) S.O. 2 F(LiFSI), LiPF 6 2. The lithium ion battery cell of claim 1, wherein the mole fraction ratio of LiFSI to LiFSI ranges from about 100:1 to about 1:1.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2009231261A

  • Lithium ion secondary battery and using method thereof

    JP2015095320A

  • Electrolytic solution for nonaqueous electrolyte battery, and nonaqueous electrolyte battery using the same

    JP2017117684A

  • Thin flexible battery

    WO2012001885A1

  • Electrical device

    WO2016098216A1